2017
DOI: 10.1038/s41598-017-03638-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinct activation modes of the Relaxin Family Peptide Receptor 2 in response to insulin-like peptide 3 and relaxin

Abstract: Relaxin family peptide receptor 2 (RXFP2) is a GPCR known for its role in reproductive function. It is structurally related to the human relaxin receptor RXFP1 and can be activated by human gene-2 (H2) relaxin as well as its cognate ligand insulin-like peptide 3 (INSL3). Both receptors possess an N-terminal low-density lipoprotein type a (LDLa) module that is necessary for activation and is joined to a leucine-rich repeat domain by a linker. This linker has been shown to be important for H2 relaxin binding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…To test the hypothesis that the two binding states of RXFP1 are associated with the binding sites in the LRRs and the linker domain, we conducted binding studies on RXFP2, which does not contain the linker-binding site (Bruell et al., 2017). We therefore first cloned a Nanoluc tag at an equivalent position of FLAG-tagged RXFP2 to Nanoluc-RXFP1, and the resulting Nanoluc-RXFP2 construct was tested for cAMP activity in response to relaxin in the same way (Figure 9A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To test the hypothesis that the two binding states of RXFP1 are associated with the binding sites in the LRRs and the linker domain, we conducted binding studies on RXFP2, which does not contain the linker-binding site (Bruell et al., 2017). We therefore first cloned a Nanoluc tag at an equivalent position of FLAG-tagged RXFP2 to Nanoluc-RXFP1, and the resulting Nanoluc-RXFP2 construct was tested for cAMP activity in response to relaxin in the same way (Figure 9A).…”
Section: Resultsmentioning
confidence: 99%
“…Relaxin potency at Nanoluc-RXFP2 was not significantly different from RXFP2 (Table 1), and similarly, the potency of TamRLX was not significantly different from relaxin at RXFP2 (Figure 9B; EC 50 = 8.46 ± 0.25 versus 8.57 ± 0.26). We previously reported the affinity of relaxin for RXFP2 as being around 10 nM using a saturation binding assay with europium-labeled H2 relaxin (Bruell et al., 2017). Similarly, here using the NanoBRET system with Nanoluc-RXFP2 titrated with TamRLX, we demonstrated that the K d was 10.74 ± 1.64 nM (Figure 9C).
Figure 9Characterization of TamRLX and Nanoluc-RXFP2 and NanoBRET Saturation Binding(A) Dose-response curves of cAMP activity in HEK293T cells expressing RXFP2 when stimulated with relaxin or TamRLX.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a RXFP2 splice variant expressed in human uterine tissue that lacks the LDLa module had intact ligand binding affinity but an impaired cAMP signaling when tested in HEK293T-RXFP2 cells (Scott et al 2006). Recent studies have shown that upon receptor binding to INSL3, the RXFP2 linker region located between the LDLa and LRRs may help to direct the LDLa domain to interact with the TM and activate the receptor together with the INSL3 A-chain (Bruell et al 2017).…”
Section: Mechanisms Of Insl3 Binding and Activation Of Rxfp2mentioning
confidence: 99%